IMF Survey, Volume 36 Issue 01. (IMF Survey; IMF Survey ;, 2007)
IMF opens African technical assistance center; interview with Raghuram Rajan; IMF weighs contingent financing; Latin American growth; Nepal seeks prosperity; link between budget institutions, fiscal outcomes; fuel subsidies; IT in Ireland, India, Israel.